EFFECT OF TRUST, EASE, AND USEFULNESS ON FINTECH REPURCHASE INTENTION AMONG UNIVERSITY STUDENTS - Winda Gunawan; Riwi Sumantyo; Novi Tri Putri (MESP–FEB UNS, 2022)
The research was conducted to determine the effect of trust, perceived ease of use, and perceived usefulness on the repurchase intention of financial technology among students at Universitas Sebelas Maret. The researchers aimed to understand how these factors influenced studen’s' decisions to continue using Cicil.co.id, a financial technology service designed to assist students with financing their educational needs. The research aimed to examine the effects of trust, perceived ease of use, and perceived usefulness on student’s repurchase intentions of Cicil.co.id, a financial technology service for educational financing, among Universitas Sebelas Maret students. Using primary data from distributed questionnaires, the study applied validity and reliability tests and multiple linear regression analysis via SPSS version 22. Findings revealed that trust and perceived ease of use significantly influenced repurchase intentions, while perceived usefulness did not.